Perfil de ácidos graxos do óleo bruto e atividade anticâncer e antimicrobiana das folhas de Stachys byzantina K. Koch - Brites, Barbara Ferreira (2022)
Stachys byzantina K Koch, whose popular name is peixinho-da-horta, is an unconventional food plant (PANC), and has been more used for food purposes, highlighting its use for medicinal purposes. Despite its recent prominence as a food plant, important information on its characteristics and properties in the food field need studies and evidence. The present research aims to determine the fatty acid profile of the crude oil from the extract of Stachys byzantina leaves, to evaluate the antimicrobial capacity and its anticancer activity. The leaves were collected at Horta Flor do Cerrado in Campo Grande, MS. The fatty acid profile was determined by chromatographic analysis, its characterization was carried out according to the quality and identity indices of the crude oil: iodine value, acidity index and peroxide value. The experiments were performed in triplicate, statistically analyzed and organized in tables and graphs. To evaluate the anticancer activity, the cytotoxicity assay with the SRB dye was used and for the antimicrobial activity, the disk diffusion test and the determination of the minimum inhibitory concentration (MIC) were used. The results obtained showed that the crude oil is mainly composed of polyunsaturated fatty acids, with alpha linolenic acid, linoleic acid and palmitic acid being its main components. In the spectrometric analysis UV-Vis crude oil indicated the presence of tocopherols, carotenoids and chlorophyll. In the evaluation of the antimicrobial activity, there was no inhibition in the tested strains. In terms of anticancer activity, the crude oil showed activity on U251 (glioma), B16F10 (melanoma) and MCF7 (breast) cells and did not show cytotoxicity on normal 3T3 cells. The other extracts tested showed B3 (hydroethanolic extract) and B4 (hydroacetonic extract) activity on B16F10 (melanoma) cells, the extracts also did not show cytotoxicity on HUVEC (human umbilical cord cells).